Characteristics and Outcome of Patients With a History of Cancer Undergoing Durable Left Ventricular Assist Device Implantation. (14th November 2022) - Tie, Hongtao; Zhu, Jing; Akin, Sakir; Allen, Larry A.; Huang, Bi; Martens, Sabrina; Welp, Henryk; Simpkin, Andrew; Shi, Rui; Wu, Qingchen; Soliman, Osama; Caliskan, Kadir; et al.
Abstract : Background: Patients with cancer (patients with a history of cancer) with advanced heart failure are increasing, but unlikely to be transplanted, and left ventricular assist device (LVAD) is an alternative strategy. This study investigates the characteristics and outcomes of patients with cancer undergoing durable LVAD. Methods: Adult patients with a history of cancer who received LVADs were identified from INTERMACS (Interagency Registry for Mechanically Assisted Circulatory Support) registry: 2008 and 2017. Characteristics and outcomes between patients with cancer and those without cancer were compared, and subgroup analyses of cancer therapy–induced cardiomyopathy (CCM) and non-CCM were also conducted. Results: Overall, 1273 (6.5%) patients had a history of cancer, including 289 (22.7%) with CCM and 984 (77.3%) with non-CCM as the primary reason for heart failure. Patients with cancer had shorter median survival (3.72 versus 3.97 years, log-rank P =0.002), and multivariable Cox and competing risk regressions revealed that a history of cancer was associated with reduced survival (hazard ratio, 1.14 [95% CI, 1.04–1.26]; P =0.005; subdistribution hazard ratio, 1.24 [95% CI, 1.13–1.36]; P< 0.001) and decreased incidence of heart transplantation. There was no significant difference in mortality between patients with CCM-induced heart failure and patients without cancer. Patients with cancer experienced an increased risk of bleeding, and age, INTERMACS profile, albumin, dialysis, and blood urea nitrogen were associated with mortality in these patients. Conclusions: A history of cancer is associated with mildly reduced survival, lower incidence of heart transplantation, and increased risk of bleeding after LVAD, whereas the survival in patients with cancer with CCM-induced heart failure is similar to those without cancer. LVAD implantation in patients with cancer is very well possible.